Emerging Methods in the Identification of Bacterial Respiratory Tract Pathogens - Kiaghobadi, Flora; Dehshahri, Ali; Ghasemi, Younes; Morowvat, Mohammad Hossein (Recent Patents on Biotechnology, 2025)
AimsHere, we will review different bacterial causes of respiratory tract infections and discuss the available diagnostic methods. Moreover, we will provide some recently published patents and newer techniques, such as respiratory panels and omics approaches, and express the challenges in this path.BackgroundRespiratory tract infections (RTIs) include those infections that can lead to the involvement of different respiratory parts, including the sinuses, throat, airways, and lungs. Acute respiratory tract infection is the leading cause of death from infectious illnesses worldwide. According to the World Health Organization, 1.6 to 2.2 million deaths have occurred due to acute respiratory infections in children under five years of age. About 4 million people die annually from respiratory infections, 98% of which are caused by lower respiratory infections.ResultsDepending on the type of pathogen, the severity of the infection can vary from mild to severe and even cause death. The most important pathogens involved in respiratory tract infections include Streptococcus pneumoniae, Haemophilus influenzae, and Moraxella catarrhalis. The symptoms are often similar, but the treatment can vary greatly. Therefore, correct diagnosis is so important. There are several methods for diagnosing respiratory infections. Traditional tests include the culture of respiratory samples, considered the primary tool for diagnosing respiratory infections in laboratories, and less common standard tests include rapid and antigenic tests. It is essential to think that the culture method is reliable. In the original method of diagnosing respiratory infections, some bacteria were challenging to grow successfully, and many clinical laboratories needed to be equipped for viral cultures. Another issue is the time to get the results, which may take up to 7 days. Rapid and antigenic tests are faster but need to be more accurate.ConclusionThe clinical laboratories are trying to be equipped with molecular methods for detecting respiratory pathogens and identifying the genetic material of the infectious agent in these new methods as the primary method in their agenda.
Keywords: emerging techniques